Use of the Novel Hourglass Shaping Sutures to Create a Natural Middle Vault Shape as Illustrated by Three-Dimensional Modeling. Issue 6 (19th September 2022) - Racy, Emmanuel; Edery, Nathanel; Fanous, Amanda; Benmoussa, Nadia
Abstract : Summary: The middle vault plays a major aesthetic and functional role. Excessive narrowing of the middle vault can occur in the absence of appropriate middle vault reconstruction. This can result in both aesthetic flaws and functional issues. Spreader flaps combined with our hourglass shaping sutures technique yield a natural middle vault appearance and prevent unwanted functional and aesthetic complications.